2013
DOI: 10.1038/onc.2013.457
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 targets NBS1 to regulate DNA damage-induced senescence and epirubicin resistance

Abstract: FOXM1 is implicated in genotoxic drug resistance but its mechanism of action remains elusive. We show here that FOXM1-depletion can sensitize breast cancer cells and MEFs into entering epirubicin-induced senescence, with the loss of long-term cell proliferation ability, the accumulation of γH2AX foci, and the induction of senescence-associated β-galactosidase activity and cell morphology. Conversely, reconstitution of FOXM1 in FOXM1-deficient MEFs alleviates the accumulation of senescence-associated γH2AX foci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(149 citation statements)
references
References 34 publications
8
141
0
Order By: Relevance
“…FOXM1 is a dynamic cancer-associated biomarker involved in the regulation of various biological processes, including cell cycle progression, differentiation, metastasis, invasion and angiogenesis (14)(15)(16)(17)(18). In a previous study, the present authors demonstrated that FOXM1 was overexpressed in cervical cancer tissues, and its nuclear expression was observed to be correlated with the pathological grade of the tumor (19).…”
Section: Introductionmentioning
confidence: 60%
“…FOXM1 is a dynamic cancer-associated biomarker involved in the regulation of various biological processes, including cell cycle progression, differentiation, metastasis, invasion and angiogenesis (14)(15)(16)(17)(18). In a previous study, the present authors demonstrated that FOXM1 was overexpressed in cervical cancer tissues, and its nuclear expression was observed to be correlated with the pathological grade of the tumor (19).…”
Section: Introductionmentioning
confidence: 60%
“…In recent years, many studies have focused on the importance of FOXM1 in both DDR and negative senescence regulation (28)(29)(30). It has become evident that FOXM1 plays a fundamental role in DNA DSBs repair through upregulation of key DDR proteins such as RAD51, NBS1, and BRIP1 (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…It has become evident that FOXM1 plays a fundamental role in DNA DSBs repair through upregulation of key DDR proteins such as RAD51, NBS1, and BRIP1 (28,30). Likewise, various studies described a role for FOXM1 in the regulation of the senescence program, mainly through its downstream target BMI-1 (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC in both wild-type mice or in Arf(−/−)Rosa26-FOXM1 Tg mice was induced by diethylnitrosamine/phenobarbital. These HCC-bearing mice were then injected daily with the cell-penetrating ARF (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) peptide inhibitor to pharmacologically reduce FOXM1 activity. After 4 weeks of this treatment, HCC regions displayed reduced tumor cell proliferation and angiogenesis within the HCC region but not in the adjacent normal liver tissue.…”
Section: Foxm1 Acts As a Therapeutic Target Of Hccmentioning
confidence: 99%